Corn Planting Date and Depth – Impacts on Yield - G. F. Sassenrath; L. Mengarelli; X. Lin (Kansas Agricultural Experiment Station Research Reports, 2019)
Corn growth and production is dependent on environmental conditions during the growing season. Optimal corn growth occurs between 50 and 86°F. Early-season soil temperatures may reduce corn emergence. Conversely, later-planted corn may not have adequate moisture for good pollination and grain production. This research tested the impact of planting date and planting depth on corn yield. The yield decreased with later planting dates. Earlier planting dates had better yield at lower planting depths, but yield was reduced at deeper planting depths at later planting.
Keywords: corn planting; date of planting; planting depth; corn maturity; cumulative growing degree days